Moderate‐Level Prenatal Alcohol Exposure Induces Sex Differences in Dopamine D1 Receptor Binding in Adult Rhesus Monkeys. (December 2014) - Converse, Alexander K.; Moore, Colleen F.; Holden, James E.; Ahlers, Elizabeth O.; Moirano, Jeffrey M.; Larson, Julie A.; Resch, Leslie M.; DeJesus, Onofre T.; Barnhart, Todd E.; Nickles, Robert J.; Murali, Dhanabalan; Christian, Bradley T.; et al.
<x xml:space="preserve">Abstract</x> Background We examined the effects of moderate prenatal alcohol exposure and/or prenatal stress exposure on (D1R) binding in a non human primate model. The dopamine D1R is involved in executive function, and it may play a role in cognitive behavioral deficits associated with prenatal alcohol and/or stress exposure. Little is known, however, about the effects of prenatal alcohol and/or stress exposure on the D1R. We expected that prenatal insults would lead to alterations in D1R binding in prefrontal cortex (PFC) and striatum in adulthood. Methods Rhesus macaque females were randomly assigned to moderate alcohol exposure and/or mild prenatal stress as well as a control condition during pregnancy. Thirty‐eight offspring were raised identically and studied as adults by noninvasive in vivo neuroimaging using positron emission tomography with the D1 antagonist radiotracer [11C]SCH 23390. Radiotracer binding in PFC and striatum was evaluated by 2 (alcohol) × 2 (stress) × 2 (sex) analysis of variance. Results In PFC, a significant alcohol × sex interaction was observed with prenatal alcohol exposure leading to increased [11C]SCH 23390 binding in male monkeys. No main effect of prenatal alcohol or prenatal stress exposure was observed. Conclusions These results suggest that prenatal alcohol exposure results in long‐term increases in prefrontal dopamine D1R binding in males. This may help explain gender differences in the prevalence of neurodevelopmental disorders consequent to prenatal alcohol exposure.